Health effects due to exposure to polycyclic aromatic hydrocarbons from the petroleum reining industry - Montaño Soto, Myriam Tatiana; Garza Ocañas, Lourdes (UANL. Facultad de Medicina, 2014)
Introduction: Polycyclic aromatic hydrocarbons (PaH) are a group of semi-volatile organic compounds composed of 2 or more aromatic rings, generated during incomplete combustion of organic matter. These compounds have been considered as major air pollutants, and also, there is evidence of potential mutagenic and carcinogenic effects in some of them. One of the most important sources of these compounds is industry, and particularly, in processes such as aluminium or coke production, waste incineration and petrochemical and oil reining. This last process is the subject of this article, whose aim is to review the health effects in persons potentially exposed to PAH generated during petroleum reining. Methods: a descriptive review of the available literature was performed, in which PubMed was used as an information source. The following search descriptors were used: refinery, PaH, health, health impact assessment, air pollutants and environmental, as well as their translations in Spanish. Results: eleven articles were included, and most of them correspond to epidemiological studies in which a high incidence of cancer is reported. Conclusions: The reviewed studies concur that there is a signiicant relationship between the presence of oil reineries and the increase of adverse health effects of workers and people living in areas that are close to these industries, particularly, respiratory diseases and cancer. However, it is important to develop studies that simultaneously evaluate the effects on human health and the concentration of these substances in the environment, in order to establish a more direct relationship between the 2 variables.